Utilization of Cacao Pods Shells For Charcoal Briquettes - Suprapti Suprapti; Sitti Ramlah (Balai Riset dan Standardisasi Industri Pontianak, 2013)
Utilization of cacao pod shells waste into charcoal briquettes is a way to find an alternative energy that can be produced within household scale. The aim of the research is to produce charcoal briquettes from cacao pod shells and its characterization. Research was designed with two factors, which is charcoal size (30, 50, and 70 mesh) and the percentage of starch used (3, 5, and 7%). Charcoal briquette produced then tested its physical and chemical properties. In general, charcoal briquettes from cacao pod shells with a mesh of 30 and 7% starch gives the best results. This charcoal briquette have a moisture content of 6.52%, ash content 16.73%, density 0.96 g/cm3; levels of volatile matter 20.18%, bonded carbon content 56.58%, and calorific value 4163.11 cal./g. Most of the parameters have not been meet the quality standards for charcoal briquettes of the SNI, Japan, England, nor American.